2015
DOI: 10.1109/mcom.2015.7295469
|View full text |Cite
|
Sign up to set email alerts
|

Providing current and future cellular services to high speed trains

Abstract: Abstract-The demand for a broadband wireless connection is nowadays no longer limited to stationary situations, but also required while traveling. Therefore, there exist combined efforts to provide wireless access also on High Speed Trains (HSTs), in order to add to the attractiveness of this means for transportation. Installing an additional relay on the train, to facilitate the communication, is an approach that has already been extensively discussed in literature. The possibility of a direct communication b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Other studies in this environment include for example [1], [4], [7], [10], [11], [12]. These studies are primarily concerned with radio level aspects, or using LTE in general, for enabling connectivity on trains.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in this environment include for example [1], [4], [7], [10], [11], [12]. These studies are primarily concerned with radio level aspects, or using LTE in general, for enabling connectivity on trains.…”
Section: Related Workmentioning
confidence: 99%
“…For this paper, we perform studies of such an access terminal system consisting of an aggregation gateway with WiFi on the LAN side and LTE on the WAN side. In further related work, Mueller et al [11] compare the performance of using a train access terminal versus users having a direct connection, by means of simulation studies. The results show that access terminals Track Nr of Nr router Nr of Avg name Length journeys ids cellids velocity StoGbg 485 km 2380 54 5589 103 km/h StoMal 615 km 3900 36 5048 137 km/h StoKsd 325 km 1458 52 2765 135 km/h Overall 7738 97 11644 125 km/h Table I: Train route characteristics 0 50 100 150 200 Train provide the best performance, but individual connectivity is also performing well.…”
Section: Related Workmentioning
confidence: 99%
“…Using the Taylor series to approximate terms such as exp − μ th − γ h 1 / γ b 1 + γ h 1 and solving the integral in the previous expression, we obtain P…”
Section: Exact Outage Probabilitymentioning
confidence: 99%
“…Cooperative relaying has gained a lot of interest from both academic and industrial communities due to its application prospects to facilitate range-rate improvements of future wireless communication systems [1][2][3][4]. Cooperative relaying offers significant performance benefits in enabling connectivity, and increasing coverage, power saving, spectral efficiency, spatial diversity, and channel capacity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in [37] identified the critical differences between the railway communication system and the conventional cellular system with the proposed transmission schemes for the HST scenario using a two-hop network architecture. A single hop network architecture was adopted in [38], where advanced collaboration schemes were used to improve the throughput. However, with the increasing data rate requirement, the use of advanced transmission schemes and techniques at microwave bands is not enough to meet the data rate demand.…”
Section: Introductionmentioning
confidence: 99%